2018
DOI: 10.1016/j.fuel.2018.06.091
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical behavior of three algal biodiesels over wide ranges of pressure and temperature

Abstract: The knowledge of density and viscosity is important both for the optimization of diesel engines operation and the fuel quality specification. To this end, the present work focuses on the study of these thermophysical properties for three algal biodiesels. The samples were produced by transesterification of dry biomass supplied from different microorganisms, the marine strain Nannochloropsis gaditana, the freshwater strain Scenedesmus almeriensis and the freshwater cyanobacteria Spirulina platensis. The protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Regarding conductivity, it is considered to be a freshwater species [34], but it shows a high tolerance to medium concentrations of salt (0.1 M NaCl) [35]. Tetradesmus almeriensis shows a very unusual carotenoid content, especially lutein (up to 1% in d.w.) and β-carotene (0.75 mg/g) [32,36]; the starch and fatty acid content are also unusually high, with a yield of 16.7% (similar to that found in Neochloris oleoabundans) and 6% (higher than in Arthrospira platensis), respectively [33,[37][38][39].…”
Section: Ecologymentioning
confidence: 99%
“…Regarding conductivity, it is considered to be a freshwater species [34], but it shows a high tolerance to medium concentrations of salt (0.1 M NaCl) [35]. Tetradesmus almeriensis shows a very unusual carotenoid content, especially lutein (up to 1% in d.w.) and β-carotene (0.75 mg/g) [32,36]; the starch and fatty acid content are also unusually high, with a yield of 16.7% (similar to that found in Neochloris oleoabundans) and 6% (higher than in Arthrospira platensis), respectively [33,[37][38][39].…”
Section: Ecologymentioning
confidence: 99%
“…Decane and dodecane have been usually used as surrogates for fossil diesel since these are common components of fossil diesel; , the combustion characteristics for these alkanes have been widely studied, and dodecane has just about the same volatility and cetane number against fossil diesel . Experimental volumetric properties for different types of biodiesel and biodiesel blends have been reported in the literature. Zhao et al have reported thermophysical properties for binary systems constituted by hexadecane + esters (methyl butyrate, methyl decanoate, ethyl hexanoate, and ethyl heptanoate). Ferreira et al measured densities for used cooking oil biodiesel up to 30 MPa in the interval of 298.41 to 343.23.…”
Section: Introductionmentioning
confidence: 99%
“…Talavera-Prieto et al 35 measured densities of cottonseed oil biodiesel at temperatures from 278 to 358 K and pressures up to 30 MPa. NguyenThi et al 36 determined densities of waste cooking oil biodiesel and blends with diesel over ranges of the pressure of 0.1−140 MPa and temperature 293.15−353.15 K. Bessieres et al 37 studied the density of three algal biodiesels at high temperatures and pressures. In summary, the methyl ester lard 34 is the unique data set about the high-pressure density of biodiesel produced from fats.…”
Section: Introductionmentioning
confidence: 99%
“…Some traditional solid lubricants, such as graphite and MoS 2 , are not able to work effectively at elevated temperature in the fields of aerospace, aircraft, and others. Therefore, scholars have tried to prepare advanced materials for continuous lubrication in a wide-temperature range [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%